The Ability to Reduce Soil Legacy Phosphorus at a Country Scale - McDowell, Richard; Dodd, Rosalind; Pletnyakov, Peter; Noble, Alasdair (Frontiers in Environmental Science, 2020)
The build-up of soil phosphorus (P) beyond plant requirements can lead to a long-term legacy of P losses that could impair surface water quality. Using a database of 450,000 samples collected from 2001-2015 we report the level of soil P enrichment by soil type, land use and region and the time it would take for Olsen P to decline to agronomic targets (20-40 mg L-1) if P fertiliser was stopped. We also modelled the time it would take for water extractable P (WEP), an indicator of P losses in surface runoff, to decline to an environmental target (0.02 mg L-1). Some 63% of the samples were enriched beyond agronomic targets. The area-weighted median time to reach the agronomic target was predicted to occur within a year for 75% of samples but varied up to 11.8 years in some land uses. However, the area-weighted time to reach an environmental target was 26-55 years for the 50th and 75th percentile of areas. This indicates that while an agronomic target can be easily met, additional strategies other than stopping P fertiliser inputs are required to meet an environmental target.